Analisis Rasio Keuangan Sebelum dan Selama Pandemi Covid-19 pada Perusahaan yang Terdaftar pada Bursa Efek Indonesia (Studi Kasus Indeks LQ45 Periode 2018-2022) - Cindy Nur Chofifah; Anik Malikah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine whether or not there are differences in financial ratio before and during the pandemic Covid-19 in LQ45 index companies for the period January 2018- June 2022. This study uses financial ratio Current Ratio, Quick Ratio, Debt To Assets Ratio, Debt To Equity Ratio, Total Asset Turnover Ratio, Fixed Asset Turnover Ratio, Return On Asset Ratio, Return On Equity Ratio, Earning Per Share Ratio, Price Earning Ratio. The population of this study are companies listed in the LQ45 index. Sampling using Purposive Sampling method and obtained 16 companies. The data analysis method used a normality test. The results of the prove that the Current Ratio, Quick Ratio, Debt To Assets Ratio, Debt To Equity Ratio, Fixed Asset Turnover Ratio, Return On Asset Ratio, Return On Equity Ratio, Earning Per Share Ratio, and Price Earning Ratio were not different before and during the Covid-19 pandemic, while for the Total Asset Turnover Ratio there was a difference before and during the Covid-19 pandemic.Keyword: Analysis of financial ratio, current ratio, quick ratio, debt to assets ratio, debt to equity ratio, total asset turnover ratio, fixed asset turnover ratio, return on asset ratio, return on equity ratio, earning per share ratio, price earning ratio